Evaluating the Antifungal Efficacy of Cinnamon Oil for Controlling Penicillium digitatum and Enhancing Post-Harvest Orange fruit Preservation - Marwa Tahsin MuhammedSharif; Tavga Sulaiman Rashid (Zanco Journal of Pure and Applied Sciences, 2025)
Penicillium digitatum is one of the major pathogens for green mold rot in citruses and is a serious threat for postharvest disease control. P. digitatum was isolated from the infected oranges, and pathogenicity tests were conducted. The most virulent isolate was then identified by molecular analysis and confirmed 100% is P. digitatum. The in vitro efficacy of cinnamon oil as a potential antifungal agent was studied using well diffusion and minimum inhibitory concentration assay. The findings confirmed that higher concentration (5%) had a significant inhibition 90% impact on fungal growth. The GC-MS analysis showed 29 compounds, of which six major compounds were present in the highest percentages: 5H-1-Pyrindine-3-carbonitrile, 2-bromo-6,7-dihydro- (24.52%), Tolmetin (13.9%), and Palmitic acid (8.82%), 6-Acetyl-6-indolo(2,3-b)quinoxaline (7.75%), 1-Methyl-1H-pyrazolo[3,4-b]pyridin-3-ylamine (24.25%), 2,5-Ethano-2H-azocino[4,3-b]indole (7.65%). For the in vivo experiment, orange fruits were immersed in 1% cinnamon oil to assess its efficacy in extending shelf life. Shelf life and infection reduction rate were observed for 22 days, which showed that cinnamon oil was effective in resisting fungal infections while ensuring fruit quality. These results indicate that cinnamon oil is a natural and eco-friendly substitute for chemical fungicides in plant disease management and food preservation.